Soil reaction to heavily loaded rubber tracks and tyres - Ansorge, Dirk (Cranfield University, 2007)
The importance of undercarriage design with respect to its effect on soil density changes grows with the size of harvest machinery. Therefore this study elucidates the mechanics of soil displacement caused by different undercarriage systems of combine harvesters on soil. The soil displacement caused by different undercarriage systems at maximum working weight was measured by embedding tracers into the soil in both the soil bin laboratory and the field studies. The effects of different tyres, tracks, and whole undercarriage systems on soil density increase were significant. The results from whole machine systems were validated with field experiments using fish-hooks for measuring displacement on a sandy loam and a clay soil. The draught force of a tine loosening the soil after the passage of whole machines was also investigated. With an increase in speed, soil density increase was reduced. The implement tyre evaluation emphasized the importance of tyre width, diameter, and inflation pressure on soil density increase. The evaluation of whole machine systems showed that the influence of rear tyre size on additional soil density increase is larger for wheeled than for tracked undercarriage systems. The strong layer at the surface from a track is able to carry the rear tyre without further compaction of the soil below leading to an overall soil displacement similar to a wheeled machine of 1/3 of the weight. The evaluation of different track systems emphasized the effect of the number of rollers on soil physical parameters. Variations in a high belt tension range showed only small effects. A novel approach was developed determining virgin compression line parameters in-situ from contact pressure, rut and working depth enabling an easy adjustment of a model to given soil conditions and a successful prediction of soil displacement for tyres. The in-situ approach can be used for tracks, but a different VCL results. The in-situ VCL was validated with small scale plate sinkage tests and compared to results from triaxial cell testing. Results from triaxial tests showed that the VCL depends on the relation of major and minor principel stresses. Ancillary experiments were carried out to shed light on longitudinal soil movement and the influence of lugs and pressure history on soil displacement. In addition a new heuristic model involving load per perimeter length was tested and the “punching failure” of soil observed justified with theories from literature. Ancillary experiments showed that the dense layer at the surface from the tracks originates from a backward soil movement limited to the uppermost 150 mm. The lug influence of both tyres and tracks was insignificant from 200 mm depth downwards. From heuristical data analysis the load per perimeter length was identified as an important variable. Peaked pressure history caused about 1/3 more sinkage than constant contact pressures.